Optimization of a Microencapsulation Process Using Oil-In-Water (O/W) Emulsion to Increase Thermal Stability of Sulforaphane - Bustos-Cerda, R; Mahn-Osses, A; Zambrano-Ibarra, V (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Sulforaphane (SFN) is a bioactive compound widely studied for its potential applications in pharmaceutical, nutraceutical, and food industries since it offers health benefits due to its nature as a Phase 2 enzyme inducer. Its application in the food industry has been limited because SFN is unstable at high temperatures in an aqueous milieu. An option to increase SFN stability and protect it from thermal degradation is microencapsulation. The aim of this work was to optimize a microencapsulation process using oil-in-water emulsion to increase the thermal stability of SFN. The operation conditions that gave the highest entrapment efficiency were determined via experimental design and response surface methodology. Thermal degradation of microencapsulated SFN was studied at 37, 50, 60, and 70 °C. The optimum microencapsulation conditions were 8 min stirring, SFN/Gum Arabic ratio of 0.82, and surfactant/oil ratio of 1.0, resulting in an entrapment efficiency of 65%, which is the highest reported so far. The thermal stability of microencapsulated SFN was greatly enhanced compared with free SFN, with a 6-fold decrease in the degradation kinetic constant and a 41% increase in the activation energy. These results will contribute to a more efficient incorporation of SFN in various food matrices and explore new microencapsulation technologies to maximize the efficiency and stability of SFN. © 2023 by the authors.
Keywords: sulforaphane; thermal stability; entrapment efficiency; oil-in-water emulsion